2018
DOI: 10.1097/phh.0000000000000775
|View full text |Cite
|
Sign up to set email alerts
|

The Public Health Community Platform, Electronic Case Reporting, and the Digital Bridge

Abstract: At the intersection of new technology advancements, ever-changing health policy, and fiscal constraints, public health agencies seek to leverage modern technical innovations and benefit from a more comprehensive and cooperative approach to transforming public health, health care, and other data into action. State health agencies recognized a way to advance population health was to integrate public health with clinical health data through electronic infectious disease case reporting. The Public Health Community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…The enhancement of healthcare students' healthcare competencies can improve community healthcare quality and reduce the medical expenses incurred by vulnerable groups [4]. Therefore, expanding the healthcare professionals' practical experience and collaboration skills to enable them to actively cooperate with professionals from various fields by integrating their knowledge and practical skills, is an important objective of healthcare education courses [5,6]. Moreover, it is important to improve healthcare education and administration methods to strengthen learners' self-directed problem-solving and integrated thinking abilities [7].…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of healthcare students' healthcare competencies can improve community healthcare quality and reduce the medical expenses incurred by vulnerable groups [4]. Therefore, expanding the healthcare professionals' practical experience and collaboration skills to enable them to actively cooperate with professionals from various fields by integrating their knowledge and practical skills, is an important objective of healthcare education courses [5,6]. Moreover, it is important to improve healthcare education and administration methods to strengthen learners' self-directed problem-solving and integrated thinking abilities [7].…”
Section: Introductionmentioning
confidence: 99%
“…The platform enabled automated systems to pull relevant records from the EHR, and then aggregate data for visualization and analysis in an application called RiskScape [7]. A more recent example of integrating clinical data into a repository for public health surveillance was the Public Health Community Platform (PHCP), an attempt by multiple public health organizations (APHL, ASTHO, JPHIT) to standardize and develop a platform for EHR to cloudbased public health data sharing and electronic case reporting [14,15]. While the pilot study faced several challenges, it demonstrated long-term feasibility for widespread integration between clinical practice and public health.…”
Section: Electronic Health Records and Public Healthmentioning
confidence: 99%
“…[7] A more recent example of integrating clinical data into a repository for public health surveillance was the Public Health Community Platform (PHCP), an attempt by multiple public health organizations (APHL, ASTHO, JPHIT) to standardize and develop a platform for EHR to cloud-based public health data sharing and electronic case reporting. [14,15] While the pilot study faced several challenges, it demonstrated long-term feasibility for widespread integration between clinical practice and public health.…”
Section: Electronic Health Records and Public Healthmentioning
confidence: 99%